Retakan-retakan Kebudayaan: Antara Keterbatasan dan Ketakberhinggaan - Piliang, Yasraf A. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
Globalization brings about not only amazing changes but threateningleakages and ruptures to the local cultures. The flush of virtualization mayhave blurred the borders founded by the cultures and in turn confused theviews of cultural identities. The identity of 'being Indonesia'(“keindonesiaan”) is in the middle of a crisis. All the processes ofglobalisation, streams of information through the media andpostmodernity have brought great impacts on this identity. This crisis isworsened by the cultural leakages and ruptures in the whole building of theculture. There are chances of mix, amalgamation and hybridisation.Multidimensional rupture brings in external influences that should beresolved by strengthening the substance of local identity. Some localcultural principles seem to have been defoundationalised. Trans-culturalphenomena appear simultaneously with the rise of hybrid identities andways of life. All this can end up in a cultural schizophrenic showing itself inthe fluidity of identity that doesn't care about the cultural foundationsanymore.